Emotional Intelligence Among the Fourth Year Nursing Students: A cross-sectional study - Albagawi, Bander (Advances in Social Sciences Research Journal, 2018)
In an educational viewpoint, emotional intelligence(EI) continues to receive a substantial amount of attention as it assumes to prepare the students towards a better person in the workplace. The researchers’ employed quantitative-correlational approach as it aims to determine the emotional intelligence among the male and female nursing students in the fourth year level, and its relationship to their demographic information. The researchers adapted the Arabic version of the Bar-On Emotional Quotient Inventory: short (EQ-I:s). There were 72 nursing students who actively participated in the study giving an 86% response rate. The results revealed that the level of emotional intelligence of the nursing students was high (m = 3.97, SD = 0.78), on the other hand, the result of the Pearson r test indicates that there is no significant correlation between the fourth year nursing students’ emotional intelligence level and student gender (p = 0.796, r = 0.031), civil status (p = 0.497, r = 0.081), and age (p = 0.711, r = 0.044). The stress management of the nursing students received the lowest , while age, gender, and civil status have no influence to their emotional intelligence. In order for the students to emotionally responsive to the critical events in their life, a tailored stress management program to meet the diverse needs of the students is highly recommended.